Analysis and presenting the educational techniques in Machine and Deep Learning Short communication - Rahul, S; ., . (International Journal of Engineering and Technology, 2018)
This paper gives a present of general learning of deep methodology and its applications to a variety of signal and data processing schedules. It is discussed about Machine learning vs. Deep Learning a brief and which is best suited in the market, Dissimilarities, Problem handling, Interpretability, Comparative and different options between cubic centimeter and metric capacity unit and concluded by justifying deep learning is a part of Machine learning and Machine learning is a part of Artificial intelligence.Â Â